+0  
 
+1
214
1
avatar

y+w-3/4z=0 for z

off-topic
Guest Apr 24, 2017
 #1
avatar+7155 
+4

To solve for z:

\(y + w - \frac34z=0\)

 

Subtract y from both sides of the equation.

\(w - \frac34z=0-y \\~\\ w - \frac34z=-y\)

 

Subtract w from both sides of the equation.

\(- \frac34z=-y-w\)

 

Multiply both sides of the equation by -\(\frac43\)

\(z=-\frac43(-y-w) \\~\\ z=\frac43(y + w)\)

hectictar  Apr 24, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.